Fine mapping and candidate gene analysis of gynoecy trait in chieh-qua (Benincasa hispida Cogn. var. chieh-qua How) - Wang, Min; Yang, Songguang; Liu, Wei; Cao, Zhenqiang; Chen, Lin; Liu, Wenrui; Xie, Dasen; Yan, Jinqiang; Jiang, Biao; Peng, Qingwu (Frontiers in Plant Science, 2023)
Gynoecism demonstrates earlier production of hybrids, higher yield, and improves the efficiency of hybrid seed production. Therefore, the utilization of gynoecy is beneficial for the genetic breeding of chieh-qua. However, little knowledge of gynoecious related genes in chieh-qua have been reported by now. Here, we used an F2 population from the cross between gynoecious line ‘A36’ and monoecious line ‘SX’ for genetic mapping and revealed that the chieh-qua gynoecy was regulated by a single recessive gene. We fine-mapped it into 530-kb region flanking by markers Indel-3 and KASP145 on Chr.8, which harbors 8 candidate genes. One of the candidate gene Bhi08G000345, encoding a networked worked protein 4 (CqNET4), contained a non-synonymous SNP resulting in the amino acid substitution of isoleucine (ATA; I) to methionine (ATG; M). CqNET4 was prominently expressed in female flower. And only three genes related to ethylene synthesis expressed significantly various between ‘A36’ and ‘SX’. The results presented here provide support for the CqNET4 as the most likely candidate gene for chieh-qua gynoecy, which differed from the reported gynoecious genes.